The hidden danger: prolonged exposure to inorganic contaminants and kidney health in adolescents - Xiaoran Xue; Zaiqiu Zhang; Marady Hun; Min Wen; Mingyi Zhao; Qingnan He (Renal Failure)
Research on the impact of prolonged exposure to inorganic contaminants, such as perchlorate, nitrate, and thiocyanate (PNT), on the kidney health of individuals in the 12 ∼ 19 age range is lacking. We analyzed data from the United States National Health and Nutrition Examination Survey (NHANES) over the period 2005–2016 to investigate the linear relationship between chronic kidney disease (CKD)-related parameters and PNT exposure levels, and to explore population heterogeneity from multiple aspects. Weighted multiple regression analysis estimated the independent associations between water or urine exposure indicators and CKD-related parameters. We utilized stratified subgroup analysis and smooth linear fitting as supplements. Lower estimated glomerular filtration rate (eGFR) (non- or new-creatinine (CR)-adjusted), albumin-to-creatinine ratio (ACR), and blood urea nitrogen (BUN) were associated with urine PNT exposure. Water exposure may not be the primary source of PNT exposure. Females had a stronger negative association between nitrate and eGFR after non- or new-CR adjustment. With the most demographic heterogeneity, perchlorate affected eGFR, ACR, and BUN. Our findings associated urinary PNT exposure with altered renal parameters (eGFR, ACR, BUN) in adolescents aged 12-19, suggesting potential environmental health implications that warrant further investigation.